Long-term combination chemotherapy using eribulin and trastuzumab for three patients with human epidermal growth factor receptor 2-positive metastatic breast cancer - Saeki, Toshiaki (Int Cancer Conf J, 2016)
The combination chemotherapy regimen of eribulin (ERI) and trastuzumab (TRA)—the ERI-TRA regimen—has been shown to be highly tolerable for patients with recurrent or metastatic human epidermal growth factor receptor 2 (HER2)-positive breast cancer. However, no sufficient clinical evidence is available for the long-term safety profile of the regimen. We report on three patients in the Phase I combination study of the regimen, for whom the regimen could be conducted over the long term. Patient #1 was a 68-year-old woman and underwent the regimen until cycle 23. Patient #2 was a 61-year-old woman and underwent the regimen until cycle 27. Patient #3 was a 59-year-old woman and underwent the regimen until cycle 22. All these patients had undergone TRA-based combination therapy before the onset of the regimen. Any new categories of adverse events did not occur in association with the long-term combination chemotherapy. Neutropenia experienced by these patients was reversible and easily manageable by dose adjustment (interruption/delay and reduction). Neither increase in the risk of cardiomyopathy nor the worsening of peripheral neuropathy greater than grade 1 was found. The present regimen was suggested to be a novel chemotherapeutic option for patients with HER2-positive recurrent or metastatic breast cancer. The fact that the long-term ERI-TRA regimen was successfully conducted for these patients can be supplementary clinical information that is beneficial for clinical oncologists.